Effect of 24 sessions of high intensity interval training on serum levels of B-type Natriuretic Peptide (BNP) in patients with heart failure - M siufjahromi; KH ebrahim; M A babaeebeigi; H nikbakht (فصلنامه ابن سینا)
Background: Cardiac rehabilitation improves functional capacity of patients with heart failure. Therefore, we are going to investigate the effects of eight weeks high intensity interval training (HIIT) on BNP serum level in patients with heart failure. Materials and methods: Twenty four cardiovascular patients with 40-50% ejection fraction were randomly divided into exercise and control groups. Exercise protocol was performed for eight weeks, three days per week. Each session consisted of 12 × 1.5 minutes bouts of pedaling on bicycle ergometer and 8 × 1.5 minutes of running on treadmill. Between high intensity repetitions, 45 to 60 seconds of active rest with 40-60% of VO2peak were performed. Intensity of training started with 50-60% VO2peak in the first week and increased 10% each week. Finally, the intensity was conducted in 80-90% of VO2peak during the 4th to 8th weeks. Blood samples were collected before and 48 hours after the last training session in the same situation from both groups. BNP level was evaluated by human ELISA kit. Data were analyzed by paired and independent samples t-tests. Results: The result showed that, in comparison of control group, BNP level was significantly decreased in HIIT group. But BNP level was significantly increased in control group, in comparison of pre- and post-test (p<0.05). Conclusion: HIIT can improve heart failure in patients with cardiovascular disease via decreasing the BNP levels.